Towards the Creation of a New Sustainable Urban Environment: Improvement and Revitalization of Public Spaces in the Historical Centre of Macao - Zhu, Rong; Pinheiro, Francisco Vizeu (2010 International Conference on E-Product E-Service and E-Entertainment, 2010)
Contemporary urban environment is facing big changes caused by a series of synthetic factors on politics, economy, technology, society and culture. Its goals and design concepts have shifted from the fulfillment of the basic function of life into the improvement of whole qualities of cities. Forming the key part of city fabric, urban historical centre helps link scattered individual historical buildings, and retrieve urban fabric. It also takes important roles in preserving history and tradition, keeping social meanings of a place and city's sustainability. This paper briefly analyzed the historic background and current issues in Macao Historic Centre. Meanwhile, strategies and principles are proposed to improve and revitalize public spaces located in dilapidated or misused historical centre so as to provide new scientific and holistic ideas for the creation of a new sustainable environment in China.
Keywords: Asia; Cities and towns; Fabrics; Green products; History; Publishing; Urban areas